Kiblah and Daylight Performance of Soppeng and Bone Traditional House in Somba Opu Fort of Makassar - Dahniar Dahniar (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
This study conducted to identify the level of daylight illumination distribution in Buginese traditional house. The investigation of the daylight performance based on two models of traditional houses located in Somba Opu Fort of Makassar. The data is based on field measurement with light meter and observation in the buildings. The study was perfomed in two different conditions in closed and opened doors and windows, and in six measuring times from morning to afternoon. Islam influence on Buginese-Makassar result the role that the best orientation of the house faces to “kiblah” orientation. The result will show the range of light illumination and the data were analysed by comparing the results of measurement with illumination standards for houses. The result show that the different daylight performance based on the shape of window.